Influence of the oxidation state of Sn in the precursor and selenization temperature on Cu2ZnSn(S, Se)4 thin film solar cells. (February 2022) - Li, Qiulian; Sun, Shizhong; Li, Xinyu; Li, Xiang; Liu, Xiu; Zhang, Daoyong; Yu, Na; Wang, Shurong
Abstract: Kesterite Cu2 ZnSn(S, Se)4 (CZTSSe) is emerging as one of the most promising materials owing to its low-cost, non-toxicity, similar electronic properties with Cu2 (In, Ga)Se2 (CIGS). However, the current highest power conversion efficiency (PCE) for CZTSSe device is far below the CIGS because of the high open-circuit voltage (Voc ) deficit and low fill factor (FF). Here, we fabricated CZTSSe thin film from 2-methoxyethanol solutions and investigated the effects of different Sn (Sn 2+ vs Sn 4+ ) oxidation states of precursor solution and selenization temperature on the crystal quality of the CZTSSe thin film and device performances. By characterizations and analyses, we found that incomplete redox reaction caused by the off-stoichiometric component in Sn 2+ precursor solution led to the formation of detrimental secondary phases such as SnSe, Cu2 Se, and SnSe2 in the CZTSSe thin film. The existence of volatile SnSe could cause the formation of voids and thus affected the FF and Voc . The reaction from Sn 4+ precursor solution to absorber material avoided the formation of SnSe. Ultimately, the Sn 4+ thin film showed better features in terms of improving crystal quality and reducing Voc deficit that limited the efficiency of kesterite CZTSSe thin film solar cells. Besides, we demonstrated that an appropriate selenization temperature could further reduce the number of secondary phases and improve the surface morphology and crystallinity of the CZTSSe thin film. As a result, we obtained CZTSSe thin film solar cells with 8.27% PCE from the Sn 4+ precursor solution under the selenization temperature of 580 °C.